Area Deprivation and Clinical Biomarkers of Inflammation in Cancer Survivors of the National Institutes of Health All of Us Research Program - Cecily A. Byrne; Vanessa M. Oddo; Evgenia Karayeva; Greg Kopetsky; Sage Kim (Cancer Medicine)
ABSTRACT Background High neighborhood deprivation is linked to increased cancer and overall mortality. Prior studies demonstrated higher inflammation in people from high deprivation areas. The area deprivation index (ADI) is a composite measure of income, education, employment, and housing, which quantifies neighborhood deprivation. We used the All of Us dataset to test whether inflammation, measured via c‐reactive protein (CRP), albumin, and the neutrophil‐to‐lymphocyte ratio (NLR), differs by ADI in cancer survivors. Methods Our sample included individuals with a history of lung, breast, prostate, and colorectal cancer, filtered for the presence of the inflammatory biomarkers. We used quartiles of ADI based on 3‐digit zip code and biomarkers from electronic health records. We estimated the association between ADI and inflammation using adjusted logistic regression (n = 690 for CRP; n = 4242 for albumin; n = 5183 for NLR). Results The sample had a mean age of 66.2 ± 10.1 years, 63.0% were female, and 86.8% were White. Mean CRP (11.5 ± 17.5 mg/L) and NLR (3.6 ± 2.2) indicated moderate to high inflammation. In the fully adjusted model, there were 2.04 (95% CI:1.02, 4.11) and 2.17 higher odds (95% CI:1.16, 4.13) of elevated CRP when comparing quartile 4 and quartile 3, respectively, to the lowest ADI quartile. Regression models were not significant for albumin or NLR. Conclusion Area deprivation is associated with CRP, a marker of stress that may lead to a higher risk of chronic diseases among cancer survivors. Future studies using a sample of cancer survivors with a wider range of ADI may help to strengthen this association.